Linear accelerator radiosurgery for vestibular schwannomas: Results of medium-term follow-up. (3rd September 2015) - Ellenbogen, Jonathan R.; Waqar, Mueez; Kinshuck, Andrew J.; Jenkinson, Michael D.; Lesser, Tristram H. J.; Husband, David; Javadpour, Mohsen
Abstract : Background . To examine tumour control, via volume changes, and the complications of linear accelerator (LINAC)-based stereotactic radiosurgery (SRS) treatment of vestibular schwannomas (VSs) on medium-term follow-up. Methods . Between September 2003 and November 2009 fifty consecutive patients with VSs treated with SRS using a marginal dose of 12.5 Gy utilizing a LINAC equipped with a micro-multileaf collimator were identified. Evaluation included serial magnetic resonance imaging (MRI), and neurological and hearing examinations. Results . The median tumour volume at treatment was 2.4 (range: 0.24–10.59) cm 3 . The intracranial diameter of the tumours ranged between 7.7 and 28.7 (median: 15.8) mm. Follow-up MRI was available for analysis on 49 patients. The median radiological follow-up period was 5.8 (range: 1.4–9.2) years. The median tumour volume at last follow-up was 1.1 (range: 0.03–5.3) cm 3 . VS decreased in size in 45 (90%) patients, with a median reduction in tumour volume of 1.46 (range: 0.06–9.29) cm 3 or a median tumour size reduction of 59% of the baseline (range: 6–90%) in these patients. VS remained stable in 2 patients and increased in size in 2 patients. Only 1 patient (2%) required additional intervention (surgery). 15 patients had useful hearing pre-treatment; 10 post-treatment pure-tone audiograms of these patients were available. 5 (50%) patients still had useful hearing post treatment. Non-auditory adverse radiation effects included new (House–Brackmann grade II) or worsened facial nerve palsy (House–Brackmann grade II to grade V) in 2 (4%) patients and trigeminal sensory disturbance in 2 (4%) patients. Conclusions . At medium term, the vast majority of VSs treated with LINAC-based SRS exhibit tumour shrinkage. The slightly higher rate of facial nerve palsy compared with Gamma Knife surgery (GKS) results may be related to the learning curve. Other complications were similar to reported GKS results for VSs of comparable sizes.